Model Pengelolaan Keuangan Desa - Siswadi Sululing; Haruni Ode; Mohammad Gifari Sono (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This research aims to help the village head and village apparatus in the financial management of the village with the recording of financial transactions are correct and balanced to produce financial reports. This type of research is the research field to the villages which receive funds village (DD), village fund allocation (ADD), and local tax and regional levies (PDRD) fiscal year 2016 in Banggai Central Sulawesi Province. Sampling method was purposive sampling. Analysis tool used is models accounting for the village. The result of the research was the revenue village is derived funds transfer Central Government and provincial government and financial aid. Shopping village consisting of shopping areas: the Organization of Government, the implementation of village development the village, the construction of the community, community empowerment, and unexpected expenditures; accounting model villages will produce financial laporaan village that consists of budget revenues and expenditures to the realization of the budget report, the village, the village belonged to the initial wealth report, balance sheet and notes to financial statements.